Research Progress in the Field of Tumor Model Construction Using Bioprinting: A Review - Yu J; Zhang Y; Ran R; Kong Z; Zhao D; Zhao W; Yang Y; Gao L; Zhang Z (International Journal of Nanomedicine, 2024)
Jiachen Yu,1,* Yingchun Zhang,1,* Rong Ran,2,* Zixiao Kong,3 Duoyi Zhao,1 Wei Zhao,1 Yingxin Yang,4 Lianbo Gao,5 Zhiyu Zhang1 1Department of Orthopedics, the Fourth Affiliated Hospital of China Medical University, China Medical University, Shen Yang, 110032, People’s Republic of China; 2Department of Anesthesia, the Fourth Affiliated Hospital of China Medical University, China Medical University, Shen Yang, 110032, People’s Republic of China; 3China Medical University, Shen Yang, 110032, People’s Republic of China; 4General Hospital of Northern Theater Command, China Medical University, Shen Yang, 110032, People’s Republic of China; 5Department of Neurology, the Fourth Affiliated Hospital of China Medical University, China Medical University, Shen Yang, 110032, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhiyu Zhang; Lianbo Gao, The Fourth Affiliated Hospital of China Medical University, No. 4 Chongshan Road, Huanggu District, Shenyang, Liaoning, People’s Republic of China, Email zyzhang@cmu.edu.cn; lbgao@cmu.edu.cnAbstract: The development of therapeutic drugs and methods has been greatly facilitated by the emergence of tumor models. However, due to their inherent complexity, establishing a model that can fully replicate the tumor tissue situation remains extremely challenging. With the development of tissue engineering, the advancement of bioprinting technology has facilitated the upgrading of tumor models. This article focuses on the latest advancements in bioprinting, specifically highlighting the construction of 3D tumor models, and underscores the integration of these two technologies. Furthermore, it discusses the challenges and future directions of related techniques, while also emphasizing the effective recreation of the tumor microenvironment through the emergence of 3D tumor models that resemble in vitro organs, thereby accelerating the development of new anticancer therapies.Keywords: bioprinting, bioink, organoids, tumor spheroids, tumor chips